Analisis Sensifitas Ketelitian Parameter Hasil Hitung Kuadrat Terkecil - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas MIPA Universitas Gadjah Mada, 2004)
ABSTRAK In conventional surveying and mapping, distance and angle are basic quantities to determine positions on the earth surface. Those penalties are measured and then adjusted using least square method to compute the coordinates of points geometrically connected by those observed quantities. In parametric least square adjustment the point coordinates are generally treated as unknown parameters (X). For parametric adjustment, the accuracy of the unknown parameters (Cv) are affected according to particular statistic distribution by all observed quantities as represented by the weight matrix P and design matrix A. However, there is less infinmation about intensity and distribution of the effect. This research is conducted to analyse numerically the sensitivity measure of unknown parametes resulted from all observations in the quadrilateral network (triangulateration). The distances are measured using EDM RED 2L and the angles are measured using Theodolite TS-6. Computation of the weight nutria is accomplished by Mikhail model and analysis is conducted by increasing the weight of the observations to buw the sensitivity of Cy. The result .shows that different observations in the survey result in different effects on the quality of the network in which the observed distances give greatest effect on the parameters. Increasing two times the Weight of she observed. Keywords: parameter, nilai distribusi